Lichen substances from Teloschistes flavicans (Sw.) Norman: Isolation, crystal structure, and evaluation of their antibacterial activities - Ismed, Friardi; Arifa, Nurwahidatul; Nissa, Mentari Q.; Putra, Deddi P.; Orue, Analia IC.; Clegg, Jack K.; Rouaud, Isabelle; Dévéhat, Françoise L. (Narra Sains Indonesia, 2025)
Teloschistes flavicans (Sw.) Norman is a lichen known as the golden-haired lichen. This lichen has been recognized and used in herbal medicine mixtures as an antimicrobial and bioindicator of air pollution that plays a role in ecological systems. The aim of this study was to explore the potential of its secondary metabolites as antibacterial and anticancer agents, particularly against bacterial pneumonia. Two main compounds (vicacinin and parietin) were isolated with chromatography and identified by spectrometry and single-crystal X-ray diffraction. The crystallographic data of vicanicin are reported for the first time. Chromatography and recrystallization methods were used to obtain both compounds with orange (parietin) and white (vicanicin) crystals. Furthermore, these compounds were evaluated for cytotoxicity on keratinocytes (HaCaT) cells and antibacterial activity against pneumonia pathogens (Klebsiella pneumoniae ATCC 1706, Streptococcus pneumoniae ATCC 49619, Moraxella catarhalis ATCC 25240, and Staphylococcus pyogenes ATCC 19615). The cytotoxic activity of these compounds was moderate at the concentration of 50-100 µM. The antibacterial pneumonia activity was relatively weak compared to chloramphenicol. Between the two compounds, vicanicin showed stronger activity than parietin against all strains. Vicanicin was more active against Klebsiella pneumoniae and Staphylococcus pyogenes with minimum inhibitory concentrations of 156±0.77 µM and 156±0.91 µM, respectively. In this study, comprehensive molecular structures of parietin and vicanicin have been successfully elucidated, and their antibacterial and cytotoxic activities have been provided.